Analisis Studi Literatur Penyelesaian Operator Aritmatika Serta Bilangan Bulat Dengan Code Sederhana Pada Bahasa Pemrograman C++ - Ghasani Fathonia; Yahfizham Yahfizham (STIKes Ibnu Sina Ajibarang, 2024)
In this increasingly sophisticated era, technology is also very often used in any situation. The use of various types of technology is growing so rapidly that learning activities in the field of technology have emerged which are usually called programming. Programming is also very interesting in the eyes of students because there are courses that are directly related to programming, namely Programming Algorithms. In programming, there are several types of languages ​​that are often used, for example the C and C++ programming languages. The C and C++ programming languages ​​are programming languages ​​that can simplify calculations in mathematics subjects, especially in the basic concepts of Arithmetic and Integers by using integer data types which contain numbers. So this literature concept study really makes it easier for programming users and readers to better understand the C and C++ programming languages ​​in calculating basic operations of Arithmetic Operators as well as calculations with simple codes on integers.